Pulsed laser-deposited nanocrystalline GdB6 thin films on W and Re as field emitters - Suryawanshi, Sachin R.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Applied Physics A-Materials Science & Processing, 2016)
Gadolinium hexaboride (GdB6) nanocrystalline thin films were grown on tungsten (W), rhenium (Re) tips and foil substrates using optimized pulsed laser deposition (PLD) technique. The X-ray diffraction analysis reveals formation of pure, crystalline cubic phase of GdB6 on W and Re substrates, under the prevailing PLD conditions. The field emission (FE) studies of GdB6/W and GdB6/Re emitters were performed in a planar diode configuration at the base pressure similar to 10(-8) mbar. The GdB6/W and GdB6/Re tip emitters deliver high emission current densities of similar to 1.4 and 0.811 mA/cm(2) at an applied field of similar to 6.0 and 7.0 V/mu m, respectively. The Fowler-Nordheim (F-N) plots were found to be nearly linear showing metallic nature of the emitters. The noticeably high values of field enhancement factor (beta) estimated using the slopes of the F-N plots indicate that the PLD GdB6 coating on Wand Re substrates comprises of high-aspect-ratio nanostructures. Interestingly, the GdB6/W and GdB6/Re planar emitters exhibit excellent current stability at the preset values over a long-term operation, as compared to the tip emitters. Furthermore, the values of workfunction of the GdB6/W and GdB6/Re emitters, experimentally measured using ultraviolet photoelectron spectroscopy, are found to be same, similar to 1.6 +/- 0.1 eV. Despite possessing same workfunction value, the FE characteristics of the GdB6/W emitter are markedly different from that of GdB6/Re emitter, which can be attributed to the growth of GdB6 films on W and Re substrates.